Micro, small and medium enterprises and their linkage with key actors in Ethiopia: Developing entrepreneurial ecosystem mapping - Tadesse Wudu Abate; Henok Ezezew Sheferaw (Journal of Innovation and Entrepreneurship, 2023)
Since micro, small, and medium enterprises (MSMEs) are a basic source of income and employment opportunities for the least developed countries, more emphasis has recently been given to those enterprises, and a number of research studies have been conducted. Ethiopia, as one of the Least Developed countries, could also benefit from those MSMEs if the sector is supported enough. Accordingly, this research is conducted to identify the basic determinants of the performance of MSMEs in Ethiopia and to try to develop an entrepreneurial ecosystem mapping to connect those enterprises with the concerned stakeholders, which can contribute to the improvement of the performance of MSMEs. Primary data from randomly selected 400 sampled enterprises is analyzed using ordered logistic regression, and data collected from stakeholder interviews is analyzed using descriptive analysis to develop the ecosystem mapping. Accordingly, academic institutions, such as universities, financial institutions, such as banks and credit associations, non-governmental organizations, such as GIZ and Reach for Change, and government organizations are important actors in entrepreneurship in Ethiopia. Finally, the result of the ordered logit model indicates that access to finance, training, and raw materials, experience, level of education, and sectoral dummy are statistically significant factors that affect the performance of MSMEs. Based on the results, we recommend the government of Ethiopia give more emphasis to MSMEs in different forms, such as providing support in the form of financial, training, market, and raw material linkages.
Keywords: 650; Ecosystem mapping; Ethiopia; Micro; small and medium enterprises; Ordered logit model